FAKTOR KRITIKAL EFEKTIVITAS PENERAPAN QUALITY MANAGEMENT SYSTEM ISO 9001-2008 PADA INDUSTRI KOMPONEN AUTOMOTIF - Joko Sumpono; Sawarni Hasibuan (Operations Excellence: Journal of Applied Industrial Engineering, 2016)
ISO 9001 is a standard which is very well known throughout the company engaged in manufacturing in the industrial products and services even how public services. This standard is very generic so that the entire organization can implement and reconcile with other standards simultaneously. By implementing the ISO 9001 quality management system which is the frame work for the other ISO, the organization will receive some benefit. Among them, is able to make the system work in the organization to be the standard work documented. Then can improve morale of personnel because of the clarity of work in order to reach efficiency. Besides, it is understood the policies and operating procedures that apply across the organization as well as increased monitoring of the management of the work. And most importantly is monitoring of quality products and services to partner organizations and consumers. This study aims to determine the factors most strongly correlated with the effectiveness of the implementation of ISO 9001:2008 and the implications it can be seen that step - corrective and preventive measures can be set so that the application stay awake and to determine differences in the effectiveness of the implementation of the two automotive component company. Data collection conducted preliminary interviews and questionnaires factors that influence the effectiveness of the implementation of ISO 9001 by 30 respondents. The study involved two companies that manufacture automotive components for discussions initial interviews and questionnaires weighting on internal and external factors. The analytical method used in this study is the Spearman correlation analysis and comparative study on two samples. The analysis of this study is exogenous factor with competence indicator of government or agency authorized to perform certification or inspection, legal requirements, and market forces and external does not affect the effectiveness of the application of ISO 9001: 2008.